The Capacity Evaluation and Storage Strategy of Tami Weir's Sludge Bag for Irrigation Water Demand - Winarno Winarno; Mujiati Mujiati; Dewi Ana Rusim; Bahtiar Bahtiar; Harmonis Rante (Jurnal Indonesia Sosial Teknologi, 2024)
Tami Weir is one of the weirs that has a vital role in human life. Sandtraps have an essential role in the operation of Tami bending. The objective of the evaluation and strategy for holding the Tami Weir sandtrap for irrigation water needs is to know the capacity of the Tami Weir sandtrap, the operation of the Tami Weir sandtrap, and the performance of the Tami Weir sandtrap. The method and technique for collecting data in this research is that data analysis is carried out after all the data has been collected. The results are adjusted to the purpose of writing and presented as conclusions. The results of this research are the capacity of the sandtrap during the flushing period, namely that a sediment volume of 73,134 m3 was obtained with a flushing time of fourteen (14) days. During deposition in mud pockets, the water speed will increase, and the deposition process will begin to decrease; at that time, the sediment will enter the channel. To overcome this situation, the sandtrap must be drained. The performance of the sandtrap at Tami Dam has decreased, where there is much alluvial sediment. The performance of sandtrap at Tami Weir cannot operate correctly due to the large number of sediment deposits, which are as high as the drain gate's threshold, making hydraulic draining impossible